ANALISIS KINERJA PELAKSANAAN ANGGARAN BELANJA BADAN PERENCANAAN PEMBANGUNAN DAERAH PROVINSI JAWA TIMUR - Rosidah, Nofi; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the performance of theimplementationof Budget Expenditure of Development Planning Agency at Sub-National Level of East Java in 2012-2015. The budget performance assessment can be known after the use and the absorption of the budget to carry outtheprograms and activities which exist in Development Planning Agency at Sub-National Level of East Java Province, in achieving the efficiency and the effectiveness of performance. Based on the result of the analysis of variance, it can be seen that the expenditure in 2012 is 91.36%; in 2013 is 91.67%; in 2014 is 88.94%; in 2015 is 91.57%. Meanwhile,theaspects of expenditure growth in 2012-2013 periods is 17.39%; in 2013-2014 is 15.9%; and in 2014-2015 is 9.78%. Based on the result of the analysis of the harmony and the efficiency and the effectiveness of the expenditure, it can be concluded that the performance should be improved in managing the localgovernmentbudget, so that the efficiency and the effectiveness of the performance of the implementation of the budget expenditure can be improved.Keywords: Budget Expenditure, Performance Assessment, Efficiency, Effectiveness.